Make or Buy: Case Study of 3D Printing Spare Parts Adoption - Damur Rochman, Didit; Anwar, Asep (International Journal of Psychosocial Rehabilitation, 2020)
3D printing technology opens up the possibility of manufacturing industry to make own spare parts for machinery instead procure to vendors. Limitations of 3D-printed spare parts mostly on physical characteristics have to get attention, and assessments of spare parts that can be printed are presented. In this paper, we also discussed factor factors as a framework to help make decisions on whether a company should make 3D-printed parts or buy from vendors. Case study on three companies at textiles, pharmaceuticals and machining sectors found that adoption of 3d print technology to make spare parts for their operation is inevitable as long as low volume and frequency and at cost 40- 60% of buying products. Major risks that face using 3D printing are reliability and quality products at initial period adoption, which eventually will decrease as gaining more knowledge on implementation time.